GE_GERICHTE P/6413/2022 vom 2. Juli 2025 - GE Cour de justice (2025)
PERSONNE PROCHE;HÉRITIER;HOMICIDE PAR NÉGLIGENCE;OMISSION;LÉSION CORPORELLE;BRIGANDAGE | CPP.121; CPP.110; CPP.319; CP.127; CP.12; CP.11; CP.140; CP.125; CP.156